The Debt Equivalence of Leases: An Empirical Investigation. - Bowman, Robert G. (The Accounting Review, 1980)
ABSTRACT: This study empirically investigates the relationship of capital leases to the market risk of lessees. The capitalized value of leases, as reported to the SEC under ASR-147, was used to measure the value of lease obligations. A multiple regression model was tested with market risk (β) as the dependent variable and an, accounting β, debt-to-equity ratio and leases-to-equity ratio as independent variables. Initial tests found the lease variable was not significantly associated with market risk. However, the leverage and lease variables were highly correlated. Two tests were developed to overcome the multicollinearity problem. Both tests found that when the multicollinearity was controlled, leases made a significant contribution to the association tests on market risk.